Eco-procurement strategies for environmentally conscious manufacturers. Issue 1 (1st December 2008) - Pochampally, Kishore K.; Nukala, Satish; Gupta, Surendra M.
Eco-procurement is about integrating environmental considerations into purchasing decisions. The advantages of this practice include cost savings, conservation of natural resources and energy, and compliance with environmental laws and regulations. While eco-procurement traditionally refers to customers (including companies) buying products containing recycled content, production of those products requires involvement of environmentally conscious manufacturers that must procure and reprocess used products containing recyclable content. In other words, eco-procurement in a supply chain refers as much to manufacturers as it does to customers. To this end, this paper addresses the following two crucial issues, and proposes a quantitative decision-making strategy for each of them: (1) which products must be chosen from a set of candidate-used products containing recyclable content? and (2) which suppliers, viz. companies that collect and sell the chosen used products, must be selected for eco-procurement?